The Effectiveness of Expressive Art Therapy to Increase Resilience in Sexual Violence Victim - Vrisaba, Nanda Audia; Rahmasari, Diana; Anggara, Onny Fransinata (Universitas Negeri Padang, 2023)
Sexual violence often occurs, not only within the family, social, and educational institutions. Sexual violence victims frequently experience various unpleasant impacts, such as physical, psychological, and social impacts. However, the are expected to be able to defend themselves overcome, go throught, to survive and be able to return to their normal condition after they experienced an unpleasant experience. This study aims to (1) design expressive art therapy that can be applied to sexual violence victims to increase their resilience skill; (2) to knowing the effectiveness of expressive art therapy in increase resilience skill, especially for sexual violence victims. The research design used was a mixed method research design with an explanatory sequenstial designs. The research subjects consisted of a single subject case with the A-B method, with measuring the baseline and conditions when the treatment was carried out. The results show that expressive art therapy is effective in increasing the resilience of victims of sexual violence. This is indicated by an increase in scores in baseline conditions and after treatment was given. Keywords: Expressive Art Therapy, Resilience, Sexual Violence, Victims, Mixed Method